Modern view on comprehensive approach to assistance persons with violations of the support-engine apparatus in adolescence - S. I. Kolomiyets (Kazimierz Wielki University, 2015)
It is known that scoliosis is one of the diseases of the musculoskeletal system, often affects children and adolescents. Along with the problematic solution of orthopedic issues, the psychosocial aspect remains important, in particular, the study of the features of the formation of the internal picture of scoliotic disease in adolescents, its prerequisites and the impact on the process of helping patients with scoliosis. The purpose of this study was the study of existing research on the organization of comprehensive medical and psychological and socio-pedagogical assistance to people with musculoskeletal disorders in adolescence. In the article the author emphasizes that the study of the psychological characteristics of children suffering from musculoskeletal disorders constitutes an important prerequisite for the development of an individual comprehensive program for the medical rehabilitation of adolescents in order to achieve the most effective result of treatment, reduce disability, and successfully integrate the child in social space.